TAFSĪR AL-JALĀLAIN DAN BAHASA MADURA - Ahmad Zaidanil Kamil (Lajnah Pentashihan Mushaf Al-Qur'an, 2020)
This article studies local elements being exist in the Madurese translation of Qur’anic Exegesis of Jalālain by Abdul Majid Tamim. By using Gadamer’s hermeneutics, this article argues the local elements in terms of its writing and translation styles as well as its contents are being used in this work. To be seen from its writing style, this work uses Madurese pegon and gandul meaning which reflects the author personality that the author was the keeper of the pesantren tradition. The method of his translation is both literal and interpretative translation. Majid Tamim seemed to be responsive to the social problems that happened in his surrounding. Some of the examples he tauched are the carok local tradition, the use of rice for the fidyah payment, and the importance of keeping the pesantren tradition. These local elements were formed asthe result of Tamim’s dialogues with the cultural, religious and linguistic background as his reference in one hand and his dialogue with the heritage of language, that of religious system and that of social and cultural of the Madurase where he lived on the other. This Qur’anic translation also proves the existence of the ulama of the pesantren in Java and Madura networks which is linked to the Middle East. KeywordsLocality, Tafsīr al-Jalālain, Majid Tamim, Madura.